ChemInform Abstract: Synthesis of Novel 2H, 8H‐Pyrano[2, 3‐f]chromene‐2, 8‐diones from 8‐Formyl‐7‐hydroxy‐4‐methylcoumarin. Issue 1 (7th January 2014) - Al‐Kawkabani, Ahmed; Boutemeur‐Kheddis, Baya; Makhloufi‐Chebli, Malika; Hamdi, Maamar; Talhi, Oualid; Silva, Artur M. S.
Abstract The synthesis of 8‐formyl‐7‐hydroxy‐4‐methylcoumarin (III) is developed and the condensation with various activated methylene compounds is demonstrated.